Spontaneous isolated superior mesenteric artery dissection: Systematic review and meta-analysis. (June 2019) - Karaolanis, Georgios; Antonopoulos, Constantine; Tsilimigras, Diamantis I; Moris, Dimitrios; Moulakakis, Konstantinos
Objectives: Spontaneous isolated superior mesenteric artery dissection (SISMAD) is a rare disease with an incidence of 0.06%. The purpose of the meta-analysis was to identify the outcomes associated with the various treatment options in the management of asymptomatic and symptomatic patients with SISMAD. Methods: Eligible studies were selected by searching PubMed, EMBASE, and Cochrane Library. Endpoints were outcome of asymptomatic patients treated conservatively, resolution of symptoms according to the treatment approach, rate of symptomatic patients switched from conservative to the endovascular and/or open repair, characteristics of the dissected lesion, and findings regarding the remodeling of superior mesenteric artery. Results: We identified 30 studies including 729 patients. Among them, 608 (83.4%) were symptomatic and were managed with conservative (438/72%), and/or endovascular (139/22.8%) and/or open treatment (31/5%). The remaining were asymptomatic and they were treated solely conservatively. A high rate of resolution of symptoms (92.8%) was noted for patients treated conservatively. Conversion from conservative treatment to either endovascular or open procedure was required in 12.3% and 4.4%, respectively. Resolution of symptoms was observed in 100% for those treated with open procedure and 88.8% for those treated endovascularly. The pooled rate of bowel ischemia in patients treated conservatively was 3.75% (95% confidence interval = 1.15–7.27). Complete remodeling was achieved in 32% and partial in 26% of those who were treated conservatively. Conclusions: The majority of symptomatic patients with SISAMD were treated conservatively and showed an uncomplicated course and only a small percentage required conversion to endovascular or open repair. This might highlight the benign course of the disease.